A dynamic vehicle routing problem based on real-time traffic information. (10th November 2010) - Zhao, Xin; Goncalves, Gilles; Dupas, Remy
We treat the dynamic vehicle routing problem with time windows (DVRPTW) in the context of real-time traffic information. We integrate traffic information obtained in real time to change the speed profile according to the accidents on the road network (congestion, etc.). The travel times are based on a time-dependent model in which the travel speeds are step functions. This model is enriched with an exponential smoothing function able to calculate the forecasted speed. The analysis of the results of these experiments shows that our method with real-time traffic information provides a good performance, a better robustness against a simple model with time dependent travel time.